2013
DOI: 10.4238/2013.november.18.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibition of MEK pathway on 5-aza-deoxycytidine-suppressed pancreatic cancer cell proliferation

Abstract: ABSTRACT. Pancreatic adenocarcinoma is a lethal disease because it is inoperable at the time of diagnosis. Therefore, the search for new therapeutic approaches is critical. The abnormal expression of the mitogen-activated protein kinase/extracellular signal-regulated kinase (MEK) pathway and alteration in epigenetic modification (DNA methylation and acetylation of histones) is a common feature in the majority of human pancreatic adenocarcinomas. Because DNA methyltransferase levels are regulated by the MEK pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The results revealed that 1 µM DAC significantly promoted the invasion and migration of the MGC803 cells, although it failed to elicit a response in the SGC7901 gastric cancer cell line. Consistently with previously published studies (31,32), DAC inhibited the proliferation of each cell line, without any marked difference in its effectiveness (Fig. 1C).…”
Section: Decitabine Promotes the Invasion And Migration Of Mgc803 Gassupporting
confidence: 92%
“…The results revealed that 1 µM DAC significantly promoted the invasion and migration of the MGC803 cells, although it failed to elicit a response in the SGC7901 gastric cancer cell line. Consistently with previously published studies (31,32), DAC inhibited the proliferation of each cell line, without any marked difference in its effectiveness (Fig. 1C).…”
Section: Decitabine Promotes the Invasion And Migration Of Mgc803 Gassupporting
confidence: 92%
“…More recently, 5-AZA-dC was tested in an aggressive stroma-rich mouse model of pancreatic adenocarcinoma 43 . Wang and coworkers also showed that the MEK inhibitor PD98059 potentiated the capability of 5-AZA-dC to mediate growth arrest in pancreatic cancer cells 44 . Currently, a phase II trial is recruiting participants to determine the effect of 5-AZA (oral azacytidine) on progression-free survival and outcomes in patients with resected pancreatic adenocarcinoma at high risk of recurrence 45 .…”
Section: Discussionmentioning
confidence: 98%
“…5-aza-2’deoxycytidine (DAC) has been tested in solid tumors including breast and gastric cancers, and PDAC; but as a monotherapy it has limited success [ 40 42 ]. DAC was used in combination either with a MEK inhibitor, Emodin, or IFN-gamma to successfully inhibit PDAC models [ 43 45 ]. Thus, additive inhibition was achieved with the use of epigenetic modulators and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%